Representation of the Context of Petik Laut (Sea-Picked) Traditions in the Macapat Mursada Text - Khothibhatul Ummah; Suryadi Suryadi (ETNOSIA : Jurnal Etnografi Indonesia, 2019)
This article aims to analyze a series of Petik Laut traditions that are the background for the emergence of the Mursada song text. Culture that is continuously carried out will form a tradition. One of the traditions found in Indonesia is the tradition of Petik Laut carried out in Muncar. Another term for the sea quotation is charity marine coastal communities. In its implementation, the Petik Laut tradition has several series of events that must be carried out. The series of events became the background for the emergence of the Mursadasong text that was read when one day before the core event was held. This research is a qualitative descriptive study. The main data source is a series of Petik Laut traditions and tembang macapat texts. The provision of data is obtained by observation-participation techniques, interviews, and document analysis.  The data were analyzed using linguistic anthropological theory to find out how the context of the tradition of seas was based on the emergence of the text of the Mursadasong in the Muncar fishing community. The results showed that the context of the sea-picking tradition behind the emergence of the text of the Mursadasong was the opening, the macapatan, the ider bumiand the release of offerings, and the pilgrimage of the grave.